Australian Muslim men balancing work, family and religion:a positive look at a negative issue. Issue 1 (28th January 2014) - Sav, Adem; Harris, Neil; Sebar, Bernadette
Abstract : Purpose: – This study explores how Australian Muslim men cope with potential conflict and achieve feelings of balance between their work, family and religious roles. Design/methodology/approach: – The study is guided by the interpretive paradigm and is qualitative. Data is collected from participants via semi-structured in-depth interviews ( n =20) and analysed using thematic analysis. Findings: – Personal coping strategies (e.g. making permanent changes and time management) seem more effective in coping with immediate conflict and achieving work-life balance as opposed to external ones (e.g. supervisor support). Although some of the strategies mirror existing research, their extent of use and reasons for usage by Muslim men are different. Muslim men use these strategies in a preventive manner to actively achieve work-life balance rather than just cope with episodic work-life conflict. Research limitations/implications: – The study is conducted with a small sample and the findings may not be generalizable to non-practising Australian Muslim men. To date, research has not clearly articulated how people who do not experience work-life conflict, make decisions to achieve balance. This study has a positive look at a negative issue by indicating that workers can go beyond coping with conflict and explore avenues to achieve work-life balance. The findings underscore the importance of preventive coping in achieving work-life balance and caution researchers about investigating how people cope with immediate work-life conflict only. Originality/value: – In addition to work and family roles, this study focuses on religious commitments, with religion being a largely overlooked concept within the work-family coping literature.